The Effect of Select Systemic Medications on Visual Outcomes in Diabetics With Branch Retinal Vein Occlusion. (July 2019) - Birnbaum, Faith A.; Thomas, Akshay S.; Thomas, Mridul K.; Yoon, Stephen P.; Dmitriev, Pauline; Kim, Jane S.; Powers, James H.; Khan, Kirin; Gomez-Caraballo, Maria; Fekrat, Sharon
Purpose: The purpose of this article is to evaluate the effect of systemic medications and glycemic control on the visual outcome and treatment burden in patients with diabetes and branch retinal vein occlusion (BRVO). Methods: A retrospective review was performed for patients with diabetes diagnosed with a BRVO at an academic eye center from 2009 to 2017. The use of select antihypertensives, antiplatelet agents, anticoagulants, and hypoglycemics was reviewed. Data on visual acuity (VA), central subfield thickness (CST), treatment course, and hemoglobin (Hb)A1c were obtained throughout follow-up. Results: A total of 121 eyes met criteria with a median follow-up duration of 19.4 months. The mean baseline logarithm of the minimum angle of resolution (logMAR) VA was 0.56 (Snellen equivalent, 20/72) and mean final logMAR VA was 0.5 (20/63). At final follow-up, aspirin 325 mg was associated with 4.8 fewer injections (n = 13, P = .04), insulin was associated with 3.6 more injections (n = 26, P = .04), warfarin was associated with a 79 µm increase in CST ( P = .02), and a 1% increase in HbA1c was associated with 0.86 more injections ( P < .01). Conclusions: The VA outcome of BRVO in diabetics may be worse than that of BRVO in nondiabetics. Worse diabetic control was associated with a higher treatment burden. High-dose aspirin was associated with fewer injections.